2023
DOI: 10.5194/tc-17-2851-2023
|View full text |Cite
|
Sign up to set email alerts
|

Precursor of disintegration of Greenland's largest floating ice tongue

Abstract: Abstract. The largest floating tongue of Greenland’s ice sheet, Nioghalvfjerdsbræ, has been relatively stable with respect to areal retreat until 2022. Draining more than 6 % of the ice sheet, a disintegration of Nioghalvfjerdsbræ's floating tongue and subsequent acceleration due to loss in buttressing are likely to lead to sea level rise. Therefore, the stability of the floating tongue is a focus of this study. We employed a suite of observational methods to detect recent changes at the calving front. We foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…However, it has been thinning in the last decade 5 , 6 . A recent study based on remote sensing data detected changes in the calving front, which indicate an onset of destabilization 38 . A retreat accompanied by a reduction in buttressing is thought to increase the ice discharge upstream with implications for global sea level rise.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been thinning in the last decade 5 , 6 . A recent study based on remote sensing data detected changes in the calving front, which indicate an onset of destabilization 38 . A retreat accompanied by a reduction in buttressing is thought to increase the ice discharge upstream with implications for global sea level rise.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the upper-end effect of the ice discharge of the 79NG on sea level change we conduct a series of model simulations of three scenarios by a subsequent removal of increasingly larger frontal parts of the 79NG floating tongue up to a full collapse (i.e. the removal of the entire tongue), following Humbert et al (2023). The simulations using the ice sheet model ISSM (Larour et al, 2012) and the initial state are based on a joint inversion for the basal friction coefficient on grounded ice and the ice hardness in floating ice.…”
Section: Determination Of Frontal Positions and Ice-flow Velocity Fie...mentioning
confidence: 99%
“…We investigated the impact of a possible disintegration of the floating tongue of the 79NG on the solid ice discharge based on a high-resolution setup of the ISSM model (Humbert et al, 2023). For the 79NG Mouginot et al (2015) provide an annual mean estimate of ice discharge across the grounding line of 12.0 ± 0.8 Gt a −1 for the period 2010-2015 based on remote sensing data.…”
Section: Sensitivity Of the 79ng Ice Discharge To Ice Tongue Extentmentioning
confidence: 99%
“…The true orthophoto processing follows the common photogrammetric approach and with a given surface topography of the glacier, a mosaicing of the individual images is conducted. More details of the MACS‐Polar system can be found in [3]. The resulting mosaic of a crack tip is presented in Figure 2(B).…”
Section: Observation Of Crack Fieldsmentioning
confidence: 99%
“…A detailed analysis of the crack and the calving front (Figure 2B) was conducted in [3] and has shown that this crack is also a mode I crack. Therefore, it is comparable to the situation of the crevasse field.…”
Section: Simulated Stress Fieldmentioning
confidence: 99%